2019
DOI: 10.1016/j.nicl.2019.102023
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional connectivity predicts individual language impairment of patients with left hemispheric gliomas involving language network

Abstract: HighlightsMultivariate machine learning-based prediction models of rsFCs were constructed to predict individual aphasia quotient (AQ) for LGG and HGG patients.Individual whole brain rsFCs significantly predicated AQ for LGG and HGG patients.Canonical language regions and their connections showed most predictive contributions for the LGG model, suggesting large functional reshaping.The functional network of HGG patients for language processing showed heavy dependence on connections of the left cerebro-cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 85 publications
2
25
0
Order By: Relevance
“…The ability of several rsFC ROI pairs to predict OS further extends our previous report that intratumor rsFC may be a prognostic marker for overall survival ( 18 ). This finding aligned with previous reports that brain tumors can lead to various cognitive deficits and are related to alterations in local and interhemispheric rsFC across functional networks ( 49 , 50 , 55 , 56 ). Here we showed that particular ROI-pair dependent reductions and increases in rsFC are associated with OS prediction, suggesting that connectivity alterations at specific cortical locations play an important role in influencing outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of several rsFC ROI pairs to predict OS further extends our previous report that intratumor rsFC may be a prognostic marker for overall survival ( 18 ). This finding aligned with previous reports that brain tumors can lead to various cognitive deficits and are related to alterations in local and interhemispheric rsFC across functional networks ( 49 , 50 , 55 , 56 ). Here we showed that particular ROI-pair dependent reductions and increases in rsFC are associated with OS prediction, suggesting that connectivity alterations at specific cortical locations play an important role in influencing outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…One potential limitation of our study is the generalization of the neuroplasticity strategy we described to other neurological conditions. The slow-growing feature of low-grade gliomas gives the brain the best opportunities to reorganize its networks over time, in parallel to tumor infiltration ( Desmurget et al, 2007 , Yuan et al, 2019 ). Whether homotopic plasticity may occur in sudden neurological diseases such as stroke injury or other neurological events remains to date unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, different patterns of neuroplasticity based upon various mechanisms of FC changes were correlated with different levels of cognitive disturbances: Cerebellar activity in regions with increased alteration was significantly associated with language (especially naming and comprehension scores) and MMSE Mini Mental State Examination scores [ 34 ]. Therefore, Yuan et al [ 72 ] concluded that individual language processing investigated in patients with a left hemispheric tumor using rsfMRI relied on large-scale, bilateral, cortical-subcortical, and cerebro-cerebellar circuits with various network reallocation mechanisms underpinning the different levels of language worsening in LGG and HGG patients.…”
Section: The Contribution Of Fni and Tms Mapping To Investigate Inmentioning
confidence: 99%